EVALUASI PERFORMAN TIGA JENIS RUMPUT Pennisetum sp DI BAWAH TEGAKAN TANAMAN PINUS DI LEMBANG JAWA BARAT - Sajimin Sajimin; N. D. Purwantari (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2019)
Pines are the largest tree forests in West of Java so that they are very potential to be developed as an agroforestry system. Forage crop potentially to be cultivated in the agroforestry system. The aim of the research was to study the response of the grasses grown under pines forest. The experiment was conducted at pines forest area arranged in randomized complete block design. The treatments were 3 grasses (Pennisetum purpureum cv. Taiwan, P. purpureum (local) and Pennisetum purpureophoides (king grass). Data collected were productivity, agronomic performance (plant height, tiller), forage production and quality. The result shows that shoot production of Taiwan cultivar was significantly higher than local P. purpureum. It was produced 498.4 g/clump on rainy season and 287.0 g/clump at dry season. At dry season forage production was decreased by 39,9%/ha. Nutrient composition at rainy season, crude fibre of grass was 39.89%; Ca 0.04%; P 0.26%; ash 12.46%; energy 4239.5 kcal/kg and crude protein 8.23%; while at the mid of dry season crude fibre was 38.43%; Ca 0.035%; P 0.26%; ash 11,43%; energy 3943 kcal/kg and crude protein 8.94%. Key words: pines, forestry, forage, production, quality